Modelling and simulation of earthquake‐induced changes in methane emission from the working face in an underground coal mine. Issue 3 (10th December 2021) - Qi, Qingjie; Zhang, Liang; Zuo, Shaojie; Sun, Zuo; Deng, Kai; Bi, Ruiqing; Cao, Yun
Abstract: Evidence demonstrates that unusual methane emissions in coal mines may happen after earthquakes or mine tremors. Here, a seismicity‐induced permeability change model is constructed and validated using field data from the Laohutai coalmine. The validated model is employed to explore the extent to which different peak ground velocities (PGVs), seismic acceleration coefficients, remnant coal seam methane pressures, and initial coal seam permeabilities affect earthquake‐induced methane emissions. Detailed simulation results suggest that the permeability of a coal seam subjected to earthquakes is both controlled by the dual competing mechanism of earthquake‐imposed strain and excess pore pressure. A higher PGV leads to a rapid increase in the coal seam permeability and the maximum of methane concentration in the airflow, while higher seismic acceleration coefficients could somewhat reduce them. Meanwhile, increasing the remnant methane pressure and initial permeability in a coal seam subjected to an earthquake increases the maximum of methane concentration in the airflow at working faces. These results have provided reliable guidance for how to adopt emergent measures to prevent earthquake‐triggered methane accidents in underground coal mines.